LEGAL EXPERTISE OF INVESTMENT CONTRACTS IN CONSTRUCTION: TYPICAL MISTAKES AND WAYS TO MINIMIZE RISKS - Egor Garanov (Modern American Journals, 2025)
The article is devoted to the legal expertise of investment contracts in the construction industry, with an emphasis on the analysis of typical errors that occur when concluding them. In particular, such problems include the uncertainty of the subject of the contract, unbalanced distribution of risks, the lack of clear mechanisms for dispute resolution and insufficient detailing of financial obligations. The author emphasizes that a comprehensive legal expertise is necessary to minimize risks and prevent litigation.
Keywords: Investment activity, construction industry, investment agreement, legal expertise, contractual risks, risk minimization, legal regulation, investor protection, arbitration, force majeure.